O papel do ativismo judicial em direitos e garantias fundamentais e seus limites frente à omissão dos poderes executivo e legislativo - Caporal, Hugo Chaves (2021)
The performance of the Judiciary Power has gained space in the lives of Brazilians as the ideal of citizenship advances. Seeking and defending rights became a routine in the lives of Brazilians. However, to achieve this scenario, it is necessary to have previous awareness of how these fundamental rights and guarantees arise. With this idea, the work started by taking a historical overview of these origins and the democratic model we are inserted in and how we arrived at it. In order to be able to identify and develop the reasoning, it was necessary to make a theoretical study about these essential normative texts, their problems and mainly their applicability. A search was made of where power is born, what its consequences are, who at each time had it and how its divisions resulted in the current tripartite system. In this scenario, a dialectic was proposed about a possible hierarchy of constitutional norms, both internally and when compared to international treaties to which Brazil is a signatory. It is in this context, of legislative expectations generated by Law and in the Federal Constitution of 1988 and not reached by the Executive Power that the Judiciary increases in size. From this, the analysis on the power and the way of judging was developed to understand the limits of the Judiciary Power's performance when put into effect these rights in a situation of omission or inertia of the other two powers, the main core of the formulated hypothesis. An analysis on judicial activism and judicial review was developed, with special attention to its origins and forms of application. Moving forward on this topic, the most important court in Brazil was examined. The Federal Supreme Court is seen through historical, legal and political views. For the final illustration of this scenario, we studied the case of Failure to Comply with Fundamental Precept No. 26, which, even without its own or express legislation on the subject, was the means by which the Supreme Court criminalized homophobia and transphobia by equating it with the crime of racism provided for in Law No. 7,716 / 89.